MENINGKATKAN HASIL BELAJAR PASSING ATAS BOLA VOLI MELALUI PENDEKATAN BERMAIN DENGAN MENGGUNAKAN MEDIA BALON PADA PESERTA DIDIK KELAS IV SD NEGERI 08 ROBA SAIRI KABUPATEN LANDAK JANUARI 2018 - Dangkun, Dangkun; Simanjuntak, Victor G.; Fitriana, Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the increase of learning outcomes passing on the volley ball through the approach of playing by using balloon media in students class IV SD Negeri 08 Roba Sairi Landak District January 2018. The method used is descriptive method, with Class Action Research form. Research subjects were 28 students consisting of 12 female learners and 16 boys. Data collection techniques used are tests, documentation, and questionnaires. Data were analyzed by descriptive analysis and using the mean and percentage formulas. From the results of research conducted can be concluded that the approach to play by using balloon media can improve learning outcomes passing on the volleyball. This is indicated by the acquisition of data on student learning outcomes in the first cycle with the lowest score of 46, the highest score 91, the average value 69 with less category, and 54% of classical completeness. In the implementation of cycle II obtained the data with the lowest value 62, the highest score 97, the average value 80 with excellent category, and 89% classical completeness. The result of passing learning on the students has fulfilled the success indicator that is at least the classical completeness reaches 80% with the KKM penjasorkes in class IV Negeri 08 Roba Sairi Landak District 2017/2018 academic year is 70.Keywords : Learning Outcomes Passing Up Volley Ball, Play Approach, and Balloon Media.